FINANCIAL INCLUSION IN NIGERIA: AN OVERVIEW (International Journal of Banking and Finance, 2022)
This paper analyses the level of financial inclusion in Nigeria using data from the global findex indicators. The findings reveal that Nigeria witnessed growth in several financial inclusion indicators in the early years of financial inclusion in 2014, but the benefits were not sustained in the later years, especially in 2017. Nigeria’s level of financial inclusion is very low compared to the World average. In the population group analysis, it was observed that the female, poorest, male, older and uneducated members of the population were worse- off in all indicators of financial inclusion in 2017. The implication of the observed decline in the level of financial inclusion in 2017 seems to suggest that there are barriers to financial inclusion in the post-2014 years.